Herida, muerte y resurrección. Crónica judicial del Plan General de Ordenación Urbana de Madrid (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2015)
This article is aimed to provide a general overview of the current situation of the general urban planning of Madrid, after the different judicial procedures that have challenged it and the Court Resolutions that in the last decade have hindered its validity and enforceability. With a practical –rather than academic– approach, the purpose of the article is to analyze past effects and possible future consequences of the annulment of the general plan declared in 2003, as well as the process followed in order to recover for Madrid a general plan free of suspicions of nullity.
Keywords: Planning; Enforcement of Court Resolutions; General Plan of Madrid